Molecular xenomonitoring for post-validation surveillance of lymphatic filariasis in Togo: no evidence for active transmission - Monique A. Dorkenoo; Dziedzom K. de Souza; Yao Apetogbo; Komla Oboussoumi; Degninou Yehadji; Mawèke Tchalim; Santrao Etassoli; Benjamin Koudou; Guillaume K. Ketoh; Yao Sodahlon; Moses J. Bockarie; Daniel A. Boakye (Parasites & Vectors, 2018)
Abstract Background Lymphatic filariasis (LF) is a mosquito-borne filarial disease targeted for elimination by the year 2020. The Republic of Togo undertook mass treatment of entire endemic communities from 2000 to 2009 to eliminate the transmission of the disease and is currently the first sub-Saharan African country to be validated by WHO for the elimination of LF as a public health problem. However, post-validation surveillance activities are required to ensure the gains achieved are sustained. This survey assessed the mosquito vectors of the disease and determined the presence of infection in these vectors, testing the hypothesis that transmission has already been interrupted in Togo. Method Mosquitoes were collected from 37 villages located in three districts in one of four evaluation units in the country. In each district, 30 villages were selected based on probability proportionate to size; eight villages (including one of the 30 villages already selected) where microfilaremia-positive cases had been identified during post-treatment surveillance activities were intentionally sampled. Mosquitoes were collected using pyrethrum spray collections (PSC) in households randomly selected in all villages for five months. In the purposefully selected communities, mosquitoes were also collected using human landing collections (HLC) and exit traps (ET). Collected mosquitoes were identified morphologically, and the identification of Wuchereria bancrofti DNA in the mosquitoes was based on the pool screening method, using the LAMP assay. Results A total of 15,539 mosquitoes were collected during the study. Anopheles gambiae (72.6%) was the predominant LF vector collected using PSC. Pool screen analysis of 9191 An. gambiae in 629 pools revealed no mosquitoes infected with W. bancrofti (0%; CI: 0–0.021). Conclusions These results confirm the findings of epidemiological transmission assessment surveys conducted in 2012 and 2015, which demonstrated the absence of LF transmission in Togo. The challenges of implementing molecular xenomonitoring are further discussed.